2001
DOI: 10.1002/mrm.1222
|View full text |Cite
|
Sign up to set email alerts
|

Spiral‐in/out BOLD fMRI for increased SNR and reduced susceptibility artifacts

Abstract: BOLD fMRI is hampered by dropout of signal in the orbitofrontal and parietal brain regions due to magnetic field gradients near air-tissue interfaces. This work reports the use of spiral-in trajectories that begin at the edge of k-space and end at the origin, and spiral in/out trajectories in which a spiral-in readout is followed by a conventional spiral-out trajectory. The spiral-in trajectory reduces the dropout and increases the BOLD contrast. The spiral-in and spiral-out images can be combined in several w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
484
0
3

Year Published

2003
2003
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 559 publications
(494 citation statements)
references
References 25 publications
7
484
0
3
Order By: Relevance
“…Resting‐state functional magnetic resonance imaging (rsfMRI) data were acquired while participants rested in the scanner with their eyes closed. We used a T2*‐weighted gradient echo spiral pulse sequence (Glover & Law, 2001) with the following parameters: relaxation time = 2,000 ms, echo time = 30 ms, flip angle = 89° and 1 interleave, field of view = 200, matrix = 64 × 64, in‐plane resolution = 3.125. Number of volumes collected was 216, scan time = 7:12.…”
Section: Methodsmentioning
confidence: 99%
“…Resting‐state functional magnetic resonance imaging (rsfMRI) data were acquired while participants rested in the scanner with their eyes closed. We used a T2*‐weighted gradient echo spiral pulse sequence (Glover & Law, 2001) with the following parameters: relaxation time = 2,000 ms, echo time = 30 ms, flip angle = 89° and 1 interleave, field of view = 200, matrix = 64 × 64, in‐plane resolution = 3.125. Number of volumes collected was 216, scan time = 7:12.…”
Section: Methodsmentioning
confidence: 99%
“…Stimuli were projected on a mirror mounted on the head coil using E-Prime 1.1 on a Compaq Presario computer. For each participant 880 functional images (440 per run) with 28 contiguous 4-mm-thick axial slices were collected using a T2*-sensitive spiral in/out pulse sequence (TR = 2000 ms, TE = 40 ms, flip = 90°, 3.44 × 3.44-mm inplane resolution) to minimize susceptibility dropout in ventral frontal and medial temporal brain regions (Glover and Law, 2001;Preston et al, 2004). We also acquired high-resolution and in-plane structural scans (high-resolution: T1-weighted spoiled-grass, TR = 100 ms, TE = 7 ms, flip = 90°) to aid in normalizing and visualizing the data.…”
Section: Imagingmentioning
confidence: 99%
“…Suppose the histogram of the field map, ∆ω(r i ), has K bins, and ω k and h k are the center and occurrence frequency of the kth bin. 3 Define matrices E = {e kj }, e kj = e ıω k t j , [11] P = {p kl },p kl = e ıω k τ l , [12] Q = {q lj }, [13] H = diag{h k }, [14] where i = 0, . .…”
Section: Histogram-based Least-square Time Segmentationmentioning
confidence: 99%
“…However, those pulses are undesirably long and thus compromise temporal resolution as well. On the acquisition side, using spiral in-out (12) or spiral in-in (13) trajectories recovers some signals compared to the spiral-out case, but recovery is usually partial. Last, it has also been demonstrated that intraoral and external localized shimming (14)(15)(16) can effectively improve field homogeneity and recover signals.…”
mentioning
confidence: 99%